2010
DOI: 10.1074/mcp.r900006-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Membrane Proteomics and Its Application in Clinical Cancer Biomarker Discovery

Abstract: Plasma membrane proteins that are exposed on the cell surface have important biological functions, such as signaling into and out of the cells, ion transport, and cell-cell and cell-matrix interactions. The expression level of many of the plasma membrane proteins involved in these key functions is altered on cancer cells, and these proteins may also be subject to post-translational modification, such as altered phosphorylation and glycosylation. Additional protein alterations on cancer cells confer metastatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
120
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(129 citation statements)
references
References 177 publications
2
120
0
7
Order By: Relevance
“…CD74 is a γ-subunit of the Main II class Histocompatibility Complex (MHC), hyper expression of which is often observed in malignant tumors of epithelial and mesenchymal nature (Borghese and Clanchy, 2011;Otterstrom et al, 2014). The increased expression of CD74 is associated with active metastasis and negative forecast of breast tumors development (Leth-Larsen et al, 2010;Greenwood et al, 2012;Tian et al, 2012). The previous data about studying correlation of violation of PDLIM4 expression in cells of the tumors that belong to various subtypes of BC indicates that hyperexpression of PDLIM4 is most characteristic for cells of claudindeficient subtype of the triple negative BC type (Kravchenko et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…CD74 is a γ-subunit of the Main II class Histocompatibility Complex (MHC), hyper expression of which is often observed in malignant tumors of epithelial and mesenchymal nature (Borghese and Clanchy, 2011;Otterstrom et al, 2014). The increased expression of CD74 is associated with active metastasis and negative forecast of breast tumors development (Leth-Larsen et al, 2010;Greenwood et al, 2012;Tian et al, 2012). The previous data about studying correlation of violation of PDLIM4 expression in cells of the tumors that belong to various subtypes of BC indicates that hyperexpression of PDLIM4 is most characteristic for cells of claudindeficient subtype of the triple negative BC type (Kravchenko et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that multiple subcellular locations exist for proteins in processes related to breast cancer. Leth-Larsen et al [10,11] identified 13 membrane proteins that were over-expressed and three that were under-expressed in a metastatic versus non-metastatic cell line from a total of 1919 protein entries. High ecto-5′-nucleotidase and integrin β1 expression correlated with tumor spread or distant recurrence, and poor outcome within a 10-year follow-up [10].…”
Section: Cancer Development and Proteome Profilingmentioning
confidence: 99%
“…Comprehensive profiling of the cell surface proteome provides an effective approach for the identification of commonly occurring proteins as well as proteins with restricted expression patterns in cancer (4). Monoclonal antibodies, monoclonal antibody fragments, and drug-loaded delivery systems conjugated with targeting moieties-that is, ligand-are now being used successfully for the targeting of tumors (5).…”
Section: See Page 89mentioning
confidence: 99%